2000
DOI: 10.1002/(sici)1097-4547(20000601)60:5<594::aid-jnr4>3.0.co;2-6
|View full text |Cite
|
Sign up to set email alerts
|

Functional expression of p-glycoprotein and multidrug resistance-associated protein (mrp1) in primary cultures of rat astrocytes

Abstract: Although it has been well established that the drug efflux pump P-glycoprotein (P-gp) protects the brain against the entry of cytotoxic drugs, its real in situ localization, i.e., at brain capillary endothelial cells or on astrocyte foot processes, is still controversial. The aim of this study was to compare the expression of P-gp and of multidrug resistance-associated protein (Mrp1), another drug efflux pump, in cultured neonatal rat brain astrocytes and in cultured brain capillary endothelial cells. Reverse … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
105
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 146 publications
(118 citation statements)
references
References 37 publications
12
105
1
Order By: Relevance
“…The present RT-PCR study demonstrated molecular expression of connexins (Cx32, npg Cx37, Cx43), Px1, MDR1, MRP1 and the P2X7 receptor in both non-swollen and swollen mouse astrocytes. These data are in agreement with those from previous RT-PCR studies that examined MRP1 [30,48] and the P2X7 receptor [49] in mouse astrocytes in normotonic conditions, and Px1 [50], MDR1 [31,45,51] and MRP1 [31,48] in rat astrocytes, also in normotonic conditions. However, the present study failed to detect the CFTR transcript in mouse astrocytes, in contrast to a previous report [30].…”
Section: Discussionsupporting
confidence: 92%
“…The present RT-PCR study demonstrated molecular expression of connexins (Cx32, npg Cx37, Cx43), Px1, MDR1, MRP1 and the P2X7 receptor in both non-swollen and swollen mouse astrocytes. These data are in agreement with those from previous RT-PCR studies that examined MRP1 [30,48] and the P2X7 receptor [49] in mouse astrocytes in normotonic conditions, and Px1 [50], MDR1 [31,45,51] and MRP1 [31,48] in rat astrocytes, also in normotonic conditions. However, the present study failed to detect the CFTR transcript in mouse astrocytes, in contrast to a previous report [30].…”
Section: Discussionsupporting
confidence: 92%
“…P-gp was expressed in the cortical tissues of all species (Figures 3a to 3d) as has been reported previously [24,25]. The localization of P-gp in the brain is controversial with some studies suggesting endothelial expression [24,25], while others reporting expression in the astrocytes or glial cells [26][27][28]. Nonetheless, even by using antibodies against doi: 10.5599/admet.4.3.305 265 distinct P-gp epitopes (C219 and H241), immunoreactivity was exclusively detected in capillary endothelial cells; neuronal expression of P-gp in the brain tissue was not observed in the species evaluated in the present study.…”
Section: Resultssupporting
confidence: 80%
“…15 Furthermore, astroglial expression of Mrp1 has been already observed in primary cultures of rat astrocytes, suggesting that astrocytes may also express this MDR protein during tumour transformation. 33,34 Our results show that MRP1 was expressed at both mRNA and protein level in the GL15 and 8MG cell lines, with a higher expression in the 8MG cell line. The higher MRP1 expression in the 8MG cells determined by Western blot was also found by immunocytochemistry, which revealed in addition that MRP1 expression occurs predominantly at the cell membrane of 8MG and GL15 cells.…”
Section: Discussionmentioning
confidence: 61%